Rediscovery of the restricted endemic Reseda balansae (Resedaceae) in Turkey - Çi̇lden, Emre; Yildirimli, Şi̇nasi̇; Zare, Golshan; Martín-Bravo, Santiago (Phytotaxa, 2018)
Reseda balansae Müll. Arg. (Resedaceae) is a very restricted and endangered Turkish endemic species known only from Mersin province (South Turkey), in a hotspot of biodiversity. It was first collected in 1855, and subsequently described in 1857. Afterwards, it was only collected once again in 1896. In this study we report the rediscovery of these two populations of R. balansae in Turkey more than 120 years after its last known collection. We provide a detailed revised description of this poorly known species and comments about its taxonomy (including designation of a lectotype), distribution and ecology. We also perform the first conservation assessment of the species at a global scale under IUCN categories and criteria, resulting in the proposal of the critically endangered category for the species, which apparently persists in one single population, since the type population has recently been destroyed.